The Emerging Role of PP2C Phosphatases in Tomato Immunity - Guy Sobol; Joydeep Chakraborty; Gregory B. Martin; Guido Sessa (Molecular Plant-Microbe Interactions, 2022)
The antagonistic effect of plant immunity on growth likely drove evolution of molecular mechanisms that prevent accidental initiation and prolonged activation of plant immune responses. Signaling networks of pattern-triggered and effector-triggered immunity, the two main layers of plant immunity, are tightly regulated by the activity of protein phosphatases that dephosphorylate their protein substrates and reverse the action of protein kinases. Members of the PP2C class of protein phosphatases have emerged as key negative regulators of plant immunity, primarily from research in the model plant Arabidopsis thaliana, revealing the potential to employ PP2C proteins to enhance plant disease resistance. As a first step towards focusing on the PP2C family for both basic and translational research, we analyzed the tomato genome sequence to ascertain the complement of the tomato PP2C family, identify conserved protein domains and signals in PP2C amino acid sequences, and examine domain combinations in individual proteins. We then identified tomato PP2Cs that are candidate regulators of single or multiple layers of the immune signaling network by in-depth analysis of publicly available RNA-seq datasets. These included expression profiles of plants treated with fungal or bacterial pathogen-associated molecular patterns, with pathogenic, nonpathogenic, and disarmed bacteria, as well as pathogenic fungi and oomycetes. Finally, we discuss the possible use of immunity-associated PP2Cs to better understand the signaling networks of plant immunity and to engineer durable and broad disease resistance in crop plants. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.